The impact of exercise on mental health during the COVID-19 pandemic: a systematic review and meta-analysis - Wang, Chaochao; Tian, Zuguo; Luo, Qiaoyou (Frontiers in Public Health, 2023)
Introduction Amidst the COVID-19 pandemic, there has been a global surge in mental health challenges. This study (PROSPERO CRD42023443860) aimed to investigate the impact of exercise on individuals’ mental health through systematic evaluation and meta-analysis to develop a scientific exercise program. Methods We systematically searched the literature up to August 2023 using PubMed, Web of Science, and SCOPUS. The Cochrane Risk Assessment Tool gaged the methodological quality of the included literature. Results Among the initially identified 10,343 search records, 12 studies were deemed to meet the criteria for systematic review and meta-analysis. Exercise significantly improved anxiety (SMD -0.81, 95% CI -1.10 to −0.52, p < 0.00001), depression (−1.02, 95% CI -1.42 to −0.62, p = 0.0001), stress (−1.05, 95% CI -1.33 to −0.78, p < 0.00001), and quality of life (1.11, 95% CI 0.81 to 1.41, p < 0.00001). Subgroup analyzes indicated that a single exercise session lasting 30–40 min had the most pronounced effect on reducing anxiety (−1.29, 95% CI -1.12 to −0.86, p < 0.00001) and depression (−1.76, 95% CI -2.24 to −1.28, p < 0.00001). Similarly, an exercise frequency of 3–5 times per week yielded the greatest benefits for anxiety (−1.31, 95% CI -2.15 to −0.46, p < 0.00001) and depression (−1.27, 95% CI -2.11 to −0.41, p = 0.0003). Notably, exercise exhibited its most significant impact on depression improvement in the 40–64 age group (−1.32, 95% CI -1.78 to −0.86, p < 0.00001). Moreover, exercise notably enhanced anxiety levels among individuals in middle and upper-income brackets (−0.99, 95% CI -1.11 to −0.87, p < 0.00001). Conclusion Exercise alleviated anxiety disorders, depression, stress levels, and quality of life during the COVID-19 pandemic. The most significant impact on anxiety and depression improvement is achieved by engaging in 30–40 min of exercise sessions, 3–5 times per week.